The Epistemological Distance in Learning about Teaching - Chiulli, Talitha Helen Silva (The ESPecialist, 2015)
Based on narrative inquiry and having reflective diaries as corpus, this article discusses the meanings constructed by a teacher-researcher critically reflecting upon her role as teacher in the classroom. Those diaries, part of a master’s degree research, focus on the experience of inserting principles of ESP and citizenship in a class of a Technical Integrated course in Agriculture. The analysis is based on visions of language teaching and pedagogical mediation. The meanings constructed in the language are considered through Systemic Functional Grammar, specifically through the experiential metafunction. This paper highlights the interpretation concerning the teaching role in pedagogical decisions.